2010 International Conference on Science and Social Research (CSSR 2010) 2010
DOI: 10.1109/cssr.2010.5773762
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the performance of isolated spoken Malay speech recognition using Multi-layer Neural Networks

Abstract: Abstract-This paper describes speech signal modeling techniques which are suited to high performance and robust isolated word recognition. In this study, a speech recognition system is presented, specifically an isolated spoken Malay word recognizer which uses spontaneous and formally speeches collected from Parliament of Malaysia. Currently the vocabulary is limited to 25 words that can be pronounced exactly as it written and controls the distribution of the vocalic segments. The speech segmentation task is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…The authors report an overall recognition accuracy of 85% with their own database. In [8] [50]. The speech recognition models proposed in [48] for Arabic digits and words use two variants of neural network-multi-layer perceptron and Long Short-Term Memory(LSTM).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors report an overall recognition accuracy of 85% with their own database. In [8] [50]. The speech recognition models proposed in [48] for Arabic digits and words use two variants of neural network-multi-layer perceptron and Long Short-Term Memory(LSTM).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the above discussion, it is observed that researchers are using ANN and its variants in recent times also to design ASR systems in some major languages [6], [48], [49], [50] due to their attractive characteristics as discussed in Section 1. It is to be also noted that ANN is being popularly used for digit and isolated word recognition in under-resourced languages [4], [5], [7], [8], [10]. These ANN based ASR systems are reported to deliver good recognition rates.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For classification purpose, each speech segment is assumed to correspond to a class which is labeled as 1 for FP and 2 for ELO. The number of input neuron will be calculated through the experiments by multiplying the cepstral order with the total frames as in (12) and (13) (12) Input Neuron No=CepstralOrder * TotalFrameNumber (13) The number of hidden neurons is determined by trial and error guided by Geometric Pyramid Rule (GPR) as in (14). The number of hidden neurons cannot be too many, otherwise, it cannot obtain good convergence rate [20].…”
Section: B Multilayer Perceptron (Mlp) Neural Networkmentioning
confidence: 99%
“…It is a type of speech feature involving coefficients that represent audio which are derived from a type of cepstral representation of the audio clip [17]. MFCC has been successfully used in recent speech processing related work such as in non-speech detection of dysarthric speech [18], isolated spoken speech recognition [13] and continuous speech recognition [19]. A Discrete Fourier Transform (DFT) is performed on each of the windowed speech waveform with 512 DFT.…”
Section: A Mel Frequency Cepstral Coefficientsmentioning
confidence: 99%